Investigating the workforce capacity and needs for animal disease surveillance and outbreak investigation: a mixed-methods study of veterinary services in Vietnam - Auplish, Aashima; Tra Vu, Thi Thu; Pham Duc, Phuc; Green, Alexandra C.; Tiwari, Harish; Housen, Tambri; Stevenson, Mark; Dhand, Navneet (Frontiers in Veterinary Science, 2024)
The need for strengthening national capacities for disease prevention, preparedness, and response is increasingly becoming urgent. Central to this is strengthening existing systems and workforce capacity for disease surveillance and disease outbreak response. This study aimed to evaluate the national capacity and needs of veterinary services in Vietnam in animal disease surveillance and outbreak investigation skills. A cross-sectional, convergent, mixed-methods study was conducted between November 2020 and April 2021. An online questionnaire was administered to government field veterinarians, followed by descriptive and multivariable analyses to understand field capacity, specifically levels of experience in outbreak investigation and animal health surveillance. Semistructured interviews were conducted with various stakeholders in veterinary services and interview transcripts were coded and thematically analysed. Qualitative results were used to contextualise quantitative findings from the survey. Overall, 178 field veterinary staff completed the online survey, and 25 stakeholders were interviewed. Eighty percent of respondents reported a high priority for further training in both animal disease surveillance and outbreak investigation. Training and competence were more limited at the district and commune levels, highlighting a gap in capacity at the subnational level. Reasons included a lack of in-depth training opportunities, limited access to resources and high staff turnover. Respondents who completed postgraduate qualifications in epidemiology or Field Epidemiology Training Programs were more likely to have higher levels of experience in animal health surveillance and outbreak investigation. This study identified gaps in knowledge and adoption of practices most often related to local-level or less experienced veterinary staff with limited training opportunities in epidemiology. Findings inform the prioritisation of training and planning activities to further enhance the national capacity of veterinary services in Vietnam. Underlying explanations for existing gaps in capacity include inequities in skill development and training opportunities across levels of veterinary staff, gaps in the chain of command and unequal funding across provinces.